Hubungan Pola Kuman Dan Length Of Stay Pada Pasien Abses Leher Dalam di Rsup Prof. Ngoerah Denpasar - Ayu Damayanthi; I Dewa Gede Arta Eka Putra; I Wayan Sucipta; Agus Rudi Asthuta; Made Lely Rahayu; Komang Andi Dwi Saputra (Oto Rhino Laryngologica Indonesiana, 2026)
Background: Deep neck abscess is a potentially life-threatening disorder, if not managed appropriately. Identification of the causative bacterial and factors influencing the length of hospital stay (LOS), essential for optimizing treatment strategies. Purpose: To evaluate the correlation between bacterial patterns and LOS in patients with deep neck space abscesses at Prof. Ngoerah General Hospital, Denpasar. Method: Observational analytic study with a retrospective cross-sectional design design. Data were obtained from medical records of patients diagnosed with deep neck abscess between January 2021 and December 2023, who met the inclusion criteria. Variables collected included patient characteristics, bacterial pattern based on culture results, and duration of hospitalization. The Mann-Whitney U test was used to analyze differences in LOS between bacterial groups, as the data were not normally distributed. Result: A total of 44 patients met the inclusion criteria, consisting of 27 males (61.4%) and 17 females (38.6%), with a mean age of 45.86±15.89 years. The most common diagnosis was submandibular abscess (52.3%). The distribution of bacterial pattern nearly equal between Gram-positive (47.7%) and Gram-negative (52.3%) organisms. The mean LOS in patients with Gram-negative infections was 8.70±4.92 days, compared with 6.48±4.17 days in those with Gram-positive infections. The Mann-Whitney U test demonstrated a statistically significant difference between the two groups (p < 0.05). Conclusion: There was a significant association between bacterial pattern and LOS in patients with deep neck abscess in this research. Gram-negative bacteria tend to result in longer hospitalization compared to those caused by Gram-positif bacteria.